Rare earth modified silicone rubber anti-radiation binder and preparation method thereof
By preparing regular circular sheet-like rare earth compounds in silicone rubber and combining them with composite rare earth coupling agents, the problems of uniform dispersion and efficient radiation absorption of rare earth elements in silicone rubber matrix are solved, achieving lightweight and environmentally friendly radiation resistance, suitable for circuit board protection in aerospace and nuclear energy facilities.
Patent Information
- Application Number
- CN202511030555.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-07-25
- Publication Date
- 2025-11-07
AI Technical Summary
Existing technologies make it difficult to achieve uniform dispersion and efficient radiation absorption of rare earth elements in silicone rubber matrix without introducing heavy metals, resulting in unstable material performance in space radiation environment and failing to meet the lightweight and environmental protection requirements of aerospace and nuclear energy facilities.
A specific ratio of dealcohol-type single-component room temperature vulcanizing silicone rubber and radiation-resistant rare earth compounds was mixed, and a rare earth compound with a regular circular plate-like structure was prepared by hydrothermal synthesis. Combined with a composite rare earth coupling agent, uniform doping of rare earth elements in silicone rubber and efficient radiation absorption were achieved.
It achieves highly efficient attenuation of neutrons and gamma rays, with only microcracks appearing on the material surface. It is easy to construct and suitable for circuit board protection in aerospace and nuclear energy facilities, possessing good practicality and promotional value.
Smart Images

Figure CN120904845A_ABST
Abstract
Description
TECHNICAL FIELD
[0001] The application belongs to the technical field of anti-radiation polymer materials, and particularly relates to a rare earth modified silicone rubber anti-radiation adhesive and a preparation method thereof. BACKGROUND
[0002] In the field of polymer materials, especially in the field of aerospace, rubber is widely used in manufacturing various structural components of spacecraft such as launch vehicles, satellites and spaceships due to its unique physical and chemical properties, such as good elasticity and weather resistance. When these rubber components are in service in space environment, they will be exposed to space radiation for a long time. Space radiation is mainly composed of charged particles and high-energy photons, among which high-energy photons (such as X-rays, gamma rays) and thermal neutrons can destroy the covalent bond structure of polymer materials through ionization, induce degradation reactions and generate a large number of highly chemically active free radicals. These free radicals further induce crosslinking reactions, resulting in embrittlement, loss of elasticity, surface peeling, softening and sticking, mechanical strength reduction and outgassing (release of volatile substances) of polymer materials, which may eventually cause temporary performance degradation or permanent failure of aerospace materials or devices.
[0003] In view of the above problems, domestic and foreign research institutions have carried out systematic research on improving the anti-radiation performance of rubber through various technical means. At present, the mainstream modification method is to introduce rare earth oxides and boron carbide, lead oxide and other additives into the rubber matrix through blending process, and to evaluate the anti-radiation efficiency through secondary gamma ray irradiation experiment or Monte Carlo numerical simulation method. Experimental results show that the modified rare earth oxide system indeed exhibits certain radiation protection ability. However, the blending process has significant limitations: on the one hand, it is difficult for granular rare earth oxides to achieve uniform dispersion at the microscale in the matrix, limiting the synergistic effect with the matrix material, resulting in low radiation absorption efficiency and failing to fully realize the radiation protection potential of rare earth elements on high-energy rays; on the other hand, the introduction of lead-containing additives not only increases the toxicity of the material and increases the risk of environmental pollution, but also affects the lightweight design of the spacecraft due to the increase in density, increasing the overall mass burden of the spacecraft, which is not conducive to the efficiency and economy requirements of aerospace engineering. Therefore, the existing technology cannot meet the requirements of environmental protection and lightweight while achieving efficient and uniform radiation protection, which has become a key bottleneck restricting the development of aerospace materials.
[0004] Specifically, rare earth elements such as gadolinium, samarium, europium, etc. have high neutron absorption cross section and gamma ray attenuation ability, but the compatibility of traditional particle morphology in the rubber matrix is poor, easy to agglomerate, leading to unstable microstructure of the material, and easy to produce surface cracks and performance degradation after radiation. At the same time, the existing additive system often relies on heavy metal elements, further aggravating the toxicity and weight problems of the material. In aerospace applications, such as circuit board protection, adhesives need to have the characteristics of simple construction, strong adhesion and high temperature resistance, but existing materials are difficult to meet these comprehensive requirements. Developing new rare earth-based composite materials with high-efficiency radiation resistance and environmental-friendly characteristics has become a key research direction in the field of aerospace materials. The prior art fails to provide a heavy metal-free, lightweight and uniformly dispersed silicone rubber radiation-resistant adhesive, which cannot effectively solve the problem of radiation degradation, thereby limiting its application in aerospace circuit boards, nuclear power facility equipment circuit boards and radiation-resistant parts.
[0005] In the prior art, although some attempts have been made to improve dispersibility by optimizing the blending process or introducing other fillers, the effect is limited. For example, some studies use mechanical stirring or surface modification, but it is still difficult to achieve uniform distribution at the nanoscale, resulting in instability and poor consistency of radiation protection efficiency. In addition, although the lead-containing system can improve the attenuation rate, environmental regulations are becoming increasingly stringent, and its application prospects are limited. Therefore, a new technical solution is needed to achieve uniform doping of rare earth compounds in the silicone rubber matrix and efficient radiation absorption without introducing heavy metals through structure optimization and process improvement, in order to overcome the defects of existing materials and improve the overall performance and applicability of the material. SUMMARY
[0006] The present application aims to overcome the defects of the prior art and provide a rare earth modified silicone rubber radiation-resistant adhesive.
[0007] Another object of the present application is to provide a preparation method of the above-mentioned rare earth modified silicone rubber radiation-resistant adhesive.
[0008] The technical solution of the present application is as follows:
[0009] A rare earth modified silicone rubber radiation-resistant adhesive is prepared by mixing a dealcoholized one-component room temperature vulcanized silicone rubber and a radiation-resistant rare earth compound in a ratio of 92-98wt%:2-8wt%, wherein,
[0010] The radiation-resistant rare earth compound is prepared by mixing mixed rare earth compounds, deionized water and a composite rare earth coupling agent in a mass ratio of 10:90:0.08, and the mixed rare earth compounds are prepared by reacting raw materials including gadolinium chloride, samarium chloride, europium chloride, boric acid and deionized water.
[0011] In a preferred embodiment of the present application, the dealcoholized single-component room temperature vulcanized silicone rubber is silicone rubber GD414.
[0012] In a preferred embodiment of the present application, the molar ratio of gadolinium chloride, samarium chloride, europium chloride and boric acid is 3-4:3-4:2-3:20.
[0013] Further preferably, the molar ratio of gadolinium chloride, samarium chloride, europium chloride and boric acid is 4:3:3:20.
[0014] In a preferred embodiment of the present application, the dealcoholized single-component room temperature vulcanized silicone rubber and the anti-radiation rare earth compound are mixed in a ratio of 95wt%:5wt%.
[0015] The preparation method of the above-mentioned rare earth modified silicone rubber anti-radiation adhesive comprises the following steps:
[0016] (1) preparing the mixed rare earth compound;
[0017] (2) mixing the prepared mixed rare earth compound with deionized water, adding the composite rare earth coupling agent OT6080, and sequentially performing stirring, ultrasonic treatment, suction filtration, hot deionized water washing and drying to constant weight to obtain the anti-radiation rare earth compound;
[0018] (3) mixing the anti-radiation rare earth compound with the dealcoholized single-component room temperature vulcanized silicone rubber in a nitrogen atmosphere to obtain the rare earth modified silicone rubber anti-radiation adhesive.
[0019] In a preferred embodiment of the present application, the step (1) comprises:
[0020] A. adding a mixed dispersant composed of PEG-20000 and PEG-6000 to deionized water, heating to 95°C, maintaining and stirring for 15 min, and cooling to room temperature;
[0021] B. adding aqueous solutions of gadolinium chloride, samarium chloride, europium chloride and boric acid to the material obtained in step A, stirring and mixing uniformly to a transparent solution, and sealing and storing at 38-42°C for 40-50h;
[0022] C. adding NaOH solution dropwise to the material obtained in step B, adjusting the pH of the solution to 9-10, stirring uniformly, and sealing and reacting at 4-6°C for 20-30h;
[0023] D. performing hydrothermal reaction on the material obtained in step C at 500-800°C for 45-50h; after the reaction is completed, cooling to room temperature, and sequentially performing suction filtration and hot water washing to obtain the mixed rare earth compound.
[0024] Further preferably, the ratio of boric acid to deionized water in the aqueous boric acid solution is 0.2 mol:49.6 g.
[0025] Further preferably, the mixed dispersant is composed of PEG-20000 and PEG-6000 at a mass ratio of 1:0.24.
[0026] Further preferably, the cooling rate to room temperature is 5℃ / min.
[0027] The beneficial effects of the present application are:
[0028] 1、The neutron relative attenuation rate of the adhesive of the present application can reach 71-85%, and the gamma ray relative attenuation rate can reach 88-95%, and only micro-cracks appear on the surface after irradiation, the adhesive is simple to construct, can be used in aerospace circuit boards, nuclear power equipment circuit boards and parts that need to resist radiation protection, and has good practicability and popularization value.
[0029] 2、The present application adopts a special hydrothermal synthesis process, uses samarium (Sm), gadolinium (Gd) and europium (Eu) as the main doped rare earth elements, and successfully prepares a rare earth compound with a regular circular sheet structure. By accurately controlling the reaction temperature, precursor concentration and other parameters, the uniform doping of rare earth elements in the compound lattice is realized, and the absorption cross section of the material to high-energy rays is significantly improved.
[0030] 3、Compared with traditional granular rare earth additives, the circular sheet structure has a larger geometric cross-sectional area, which can effectively increase the interaction probability with gamma rays and neutrons. This synergistic optimization of structure and performance provides a new solution for the radiation protection of spacecraft silicone rubber materials.
[0031] 4、The adhesive prepared by the present application does not contain heavy metal elements, realizes lightweight and environmental protection characteristics; through the treatment of the composite rare earth coupling agent, the dispersion uniformity of the rare earth compound in the silicone rubber GD414 is improved, and the limitations of the traditional blending process are avoided. BRIEF DESCRIPTION OF DRAWINGS
[0032] Figure 1 It is a scanning electron microscope photo of the mixed rare earth compound obtained in Example 2 of the present application.
[0033] Figure 2 It is an XRD spectrum of the mixed rare earth compound obtained in Example 2 of the present application.
[0034] Figure 3 It is a real photo of the rare earth modified silicone rubber anti-radiation adhesive prepared in Example 2 of the present application.
[0035] Figure 4The scanning electron microscope photos (Co60 irradiation meter 1M) of the rare earth modified silicone rubber anti-radiation adhesive prepared in Example 2 of the present application and the control sample (without adding anti-radiation rare earth compound) after irradiation are shown in the following table. DETAILED DESCRIPTION
[0036] The technical solutions of the present application are further described and explained in the following detailed description with reference to the accompanying drawings.
[0037] Example 1
[0038] (1) In a glass beaker, 23.56 g of deionized water was added, 1.24 g of mixed dispersant (1.0 g of PEG-20000, 0.24 of PEG-6000) was added, and heated to 95℃ for 15 min, and cooled to room temperature for standby;
[0039] (2) 0.03 mol of gadolinium chloride, 0.04 mol of samarium chloride and 0.03 mol of europium chloride were added to the material obtained in step (1) and stirred uniformly;
[0040] (3) 0.2 mol of boric acid was weighed and dissolved in 49.6 g of deionized water to prepare a solution with a concentration of 20%; then, the material obtained in step (2) was poured into the solution and stirred uniformly until a transparent solution was obtained, and then sealed and stored in a 40℃ oven for 48 h;
[0041] (4) In the material obtained in step (3), 0.5% NaOH solution was added dropwise to adjust the pH of the solution to 9-10, and then stirred uniformly and sealed and stored in a 5℃ refrigerator for 24 h for sufficient reaction;
[0042] (5) The hydrothermal reaction container containing the material obtained in step (4) was placed in a muffle furnace and subjected to hydrothermal reaction at 500℃ for 48 h; after the reaction was completed, the temperature was cooled to room temperature at a rate of 5℃ / min; the solution was poured out and subjected to suction filtration and 70℃ hot water washing in sequence to obtain a mixed rare earth compound;
[0043] (6) 10 g of the material obtained in step (5) was added to a glass bottle, 90 g of deionized water was added to prepare a solution with a concentration of 10%, and then ultrasonic treatment was performed for 10 min; then, 0.08 g of composite rare earth coupling agent (model OT6080, Fusheng brand, the same as in the following examples and comparative examples) was added, and then transferred into a high-speed stirrer at 1500 r / min and stirred for 15 min, and then subjected to ultrasonic treatment for 20 min;
[0044] (7) The material obtained in step (6) was subjected to suction filtration and washed with 70℃ hot deionized water for 3 times, and then transferred into a 110℃ oven for drying to constant weight to obtain an anti-radiation rare earth compound.
[0045] (8) Add 2 g of the anti-radiation rare earth compound obtained in step (7) to 98 g of silicone rubber GD414, and mix them in a nitrogen glove box to avoid water vapor in the air entering the silicone rubber. The mixing time is 30 min. After mixing, store the mixture in a sealed tank to obtain a rare earth modified silicone rubber anti-radiation adhesive.
[0046] Example 2
[0047] (1) In a glass beaker, add 23.56 g of deionized water, add 1.24 g of mixed dispersant (1.0 g of PEG-20000 and 0.24 g of PEG-6000), and heat to 95°C for 15 min with stirring, and cool to room temperature for standby;
[0048] (2) Add 0.04 mol of gadolinium chloride, 0.03 mol of samarium chloride and 0.03 mol of europium chloride to the material obtained in step (1), and stir until uniform;
[0049] (3) Weigh 0.2 mol of boric acid, dissolve it in 49.6 g of deionized water to prepare a 20% solution. Then, pour it into the material obtained in step (2), stir and mix until a transparent solution is obtained, and store it in a 40°C oven for 48 h;
[0050] (4) Add 0.5% NaOH solution to the material obtained in step (3) dropwise, adjust the pH of the solution to 9-10, stir until uniform, and store it in a 5°C refrigerator for 24 h to ensure complete reaction;
[0051] (5) Transfer the material obtained in step (4) to a hydrothermal reaction vessel, and place it in a muffle furnace for hydrothermal reaction at 700°C for 48 h. After the reaction is completed, cool it to room temperature at a rate of 5°C / min. Pour out the solution, and sequentially perform suction filtration and 70°C hot water washing to obtain a mixed rare earth compound (XRD as shown in Figure 1 ); Figure 2
[0052] (6) Add 10 g of the material obtained in step (5) to a glass bottle, add 90 g of deionized water to prepare a 10% solution, and ultrasonic for 10 min. Then, add 0.08 g of a composite rare earth coupling agent (model OT6080), transfer it to a high-speed stirrer at 1500 r / min, and stir for 15 min. Then, ultrasonic for 20 min;
[0053] (7) Perform suction filtration on the material obtained in step (6), wash it with 70°C hot deionized water for 3 times, and transfer it to a 110°C oven for drying to constant weight to obtain an anti-radiation rare earth compound.
[0054] (8) Add 5 g of the anti-radiation rare earth compound obtained in step (7) to 95 g of silicone rubber GD414, and mix them in a nitrogen glove box to avoid water vapor in the air from entering the silicone rubber. The mixing time is 30 min. After uniform mixing, store the mixture in a sealed tank to obtain the rare earth modified silicone rubber anti-radiation adhesive as shown in Formula (I) and (II). Figure 3 and Figure 4 Formula (I) and (II) show the rare earth modified silicone rubber anti-radiation adhesive.
[0055] Example 3
[0056] (1) In a glass beaker, add 23.56 g of deionized water, add 1.24 g of mixed dispersant (1.0 g of PEG-20000 and 0.24 g of PEG-6000), and heat to 95°C for 15 min with stirring, and cool to room temperature for standby;
[0057] (2) Add 0.04 mol of gadolinium chloride, 0.04 mol of samarium chloride and 0.02 mol of europium chloride to the material obtained in step (1), and stir until uniform;
[0058] (3) Weigh 0.2 mol of boric acid, dissolve it in 49.6 g of deionized water to prepare a 20% solution. Then, pour it into the material obtained in step (2), stir and mix until a transparent solution is obtained, and store it in a 40°C oven for 48 h;
[0059] (4) Add 0.5% NaOH solution to the material obtained in step (3) dropwise, adjust the pH of the solution to 9-10, stir until uniform, and store it in a 5°C refrigerator for 24 h to ensure complete reaction;
[0060] (5) Transfer the material obtained in step (4) to a hydrothermal reaction vessel, and place it in a muffle furnace for hydrothermal reaction at 800°C for 48 h. After the reaction is completed, cool it to room temperature at a rate of 5°C / min. Pour out the solution, and sequentially perform suction filtration and 70°C hot water washing to obtain a mixed rare earth compound;
[0061] (6) Add 10 g of the material obtained in step (5) to a glass bottle, add 90 g of deionized water to prepare a 10% solution, and ultrasonic for 10 min. Then, add 0.08 g of a composite rare earth coupling agent (model OT6080), transfer it to a high-speed stirrer at 1500 r / min, and stir for 15 min. Then, ultrasonic for 20 min;
[0062] (7) Perform suction filtration on the material obtained in step (6), wash it with 70°C hot deionized water for 3 times, and transfer it to a 110°C oven for drying to constant weight to obtain an anti-radiation rare earth compound.
[0063] (8) Add 8 g of the anti-radiation rare earth compound obtained in step (7) to 92 g of silicone rubber GD414, and mix them in a nitrogen glove box to avoid water vapor in the air entering the silicone rubber. The mixing time is 30 min. After uniform mixing, store the mixture in a sealed tank to obtain a rare earth modified silicone rubber anti-radiation adhesive.
[0064] Comparative Example 1
[0065] (1) In a glass beaker, add 23.56 g of deionized water, add 1.24 g of mixed dispersant (1.0 g of PEG-20000 and 0.24 g of PEG-6000), and heat to 95℃ for 15 min, and cool to room temperature for standby;
[0066] (2) Add 0 mol of gadolinium chloride, 0.07 mol of samarium chloride, and 0.03 mol of europium chloride to the material obtained in step (1), and stir until uniform;
[0067] (3) Weigh 0.2 mol of boric acid, dissolve it in 49.6 g of deionized water to prepare a 20% solution. Then, pour it into the material obtained in step (2), stir until uniform, and seal and store in a 40℃ oven for 48 h;
[0068] (4) Add 0.5% NaOH solution to the material obtained in step (3) dropwise, adjust the solution p H to 9-10, stir until uniform, and seal and store in a 5℃ refrigerator for 24 h, and the reaction is complete;
[0069] (5) Transfer the material obtained in step (4) to a hydrothermal reaction vessel, and place it in a muffle furnace for hydrothermal reaction at 700℃ for 48 h. After the reaction is completed, cool it to room temperature at a rate of 5℃ / min. Pour out the solution, and sequentially perform suction filtration and 70℃ hot water washing to obtain a mixed rare earth compound;
[0070] (6) Put 10 g of the material obtained in step (5) into a glass bottle, add 90 g of deionized water to prepare a 10% solution, and ultrasonic for 10 min. Then, add 0.08 g of a composite rare earth coupling agent (model OT6080), transfer it to a high-speed stirrer at 1500 r / min, and stir for 15 min. Then, ultrasonic for 20 min;
[0071] (7) Suction filter the material obtained in step (6), wash it with 70℃ hot deionized water for 3 times, and transfer it to a 110℃ oven for drying to constant weight to obtain an anti-radiation rare earth compound.
[0072] (8) Add 5 g of the anti-radiation rare earth compound obtained in step (7) to 95 g of silicone rubber GD414, and mix them in a nitrogen glove box to avoid water vapor in the air entering the silicone rubber. The mixing time is 30 min. After uniform mixing, store the mixture in a sealed tank to obtain the comparative adhesive.
[0073] Comparative Example 2
[0074] (1) In a glass beaker, add 23.56 g of deionized water, add 1.24 g of mixed dispersant (1.0 g of PEG-20000 and 0.24 g of PEG-6000), and heat to 95℃ for 15 min with stirring, and cool to room temperature for standby;
[0075] (2) Add 0.04 mol of gadolinium chloride, 0 mol of samarium chloride and 0.06 mol of europium chloride to the material obtained in step (1) and stir uniformly;
[0076] (3) Weigh 0.2 mol of boric acid and dissolve it in 49.6 g of deionized water to prepare a 20% concentration solution. Then, pour it into the material obtained in step (2) and stir to mix uniformly to a transparent solution. Store it in a 40℃ oven for 48 h;
[0077] (4) Add 0.5% NaOH solution dropwise to the material obtained in step (3) to adjust the solution p H to 9-10, stir uniformly, and store it in a 5℃ refrigerator for 24 h for sufficient reaction;
[0078] (5) Transfer the material obtained in step (4) to a hydrothermal reaction container and place it in a muffle furnace for hydrothermal reaction at 700℃ for 48 h. After the reaction is completed, cool it to room temperature at a rate of 5℃ / min. Pour out the solution and perform suction filtration and 70℃ hot water washing in sequence to obtain a mixed rare earth compound;
[0079] (6) Put 10 g of the material obtained in step (5) into a glass bottle, add 90 g of deionized water to prepare a 10% concentration, and ultrasonic for 10 min. Then, add 0.08 g of composite rare earth coupling agent (model OT6080), transfer it to a high-speed stirrer at 1500 r / min and stir for 15 min, and then ultrasonic for 20 min;
[0080] (7) Perform suction filtration on the material obtained in step (6), wash it with 70℃ hot deionized water for 3 times, and transfer it to a 110℃ oven for drying to constant weight to obtain an anti-radiation rare earth compound.
[0081] (8) Add 5 g of the anti-radiation rare earth compound obtained in step (7) to 95 g of silicone rubber GD414, and mix them in a nitrogen glove box to avoid water vapor in the air entering the silicone rubber. The mixing time is 30 min. After uniform mixing, store the mixture in a sealed tank to obtain the comparative adhesive.
[0082] Comparative Example 3
[0083] (1) In a glass beaker, add 23.56 g of deionized water, add 1.24 g of mixed dispersant (1.0 g of PEG-20000 and 0.24 g of PEG-6000), and heat to 95°C for 15 min with stirring, and cool to room temperature for standby;
[0084] (2) In the material obtained in step (1), add 0.04 mol of gadolinium chloride, 0.03 mol of samarium chloride, and 0.03 mol of europium chloride in a hydrothermal reaction vessel, and stir uniformly;
[0085] (3) Weigh 0.2 mol of boric acid, dissolve it in 49.6 g of deionized water to prepare a 20% concentration solution; then, pour it into the material obtained in step (2), stir and mix uniformly to a transparent solution, and store it in a 40°C oven for 48 h;
[0086] (4) In the material obtained in step (3), add 0.5% NaOH solution dropwise, adjust the solution p H to 9-10, stir uniformly, and store it in a 5°C refrigerator for 24 h for sufficient reaction;
[0087] (5) Transfer the material obtained in step (4) to a hydrothermal reaction vessel, and place it in a muffle furnace for hydrothermal reaction at 300°C for 48 h; after the reaction is completed, cool it to room temperature at a rate of 5°C / min; pour out the solution, and sequentially perform suction filtration and 70°C hot water washing to obtain a mixed rare earth compound;
[0088] (6) Put 10 g of the material obtained in step (5) into a glass bottle, add 90 g of deionized water to prepare a 10% concentration, and ultrasonic for 10 min; then add 0.08 g of composite rare earth coupling agent (model OT6080), transfer it to a high-speed stirrer at 1500 r / min, and stir for 15 min, and then ultrasonic for 20 min;
[0089] (7) Suction filter the material obtained in step (6), wash it with 70°C hot deionized water for 3 times, and transfer it to a 110°C oven for drying to constant weight to obtain an anti-radiation rare earth compound.
[0090] (8) 5g of the anti-radiation rare earth compound obtained in step (7) is added to 95g of the silicone rubber GD414, and the two are mixed in a nitrogen glove box to avoid water vapor in the air from entering the silicone rubber, and the mixing is performed for 30 min. After uniform mixing, the mixture is stored in a sealed tank to obtain a comparative adhesive.
[0091] The technical effects of the rare earth modified silicone rubber anti-radiation adhesive obtained in examples 1 to 3 and the comparative adhesives obtained in comparative examples 1 to 3 are shown in Table 1 below.
[0092] Table 1 Performance test indexes of the rare earth modified silicone rubber anti-radiation adhesive of the present application
[0093] Serial number Example Neutron relative attenuation rate / % Gamma ray relative attenuation rate / % Surface crack 1 Example 1 71 92 Micro crack 2 Example 2 85 95 Micro crack 3 Example 3 80 88 Micro crack 4 Comparative Example 1 22 50 Severe 5 Comparative Example 2 41 37 Moderate 6 Comparative Example 3 36 47 Moderate
[0094] The above description is only the preferred embodiments of the present application, and therefore cannot limit the scope of the present application. Equivalent changes and modifications made according to the scope of the present patent and the content of the specification should still be within the scope of the present application.
Claims
1. A rare earth modified silicone rubber radiation resistant adhesive, characterized by, The anti-radiation rare earth compound is prepared by mixing mixed rare earth compound, deionized water and complex rare earth coupling agent in a mass ratio of 10:90:0.08, and the mixed rare earth compound is prepared by reacting raw materials including gadolinium chloride, samarium chloride, europium chloride, boric acid and deionized water. The anti-radiation rare earth compound is prepared by mixing mixed rare earth compound, deionized water and complex rare earth coupling agent in a mass ratio of 10:90:0.08, and the mixed rare earth compound is prepared by reacting raw materials including gadolinium chloride, samarium chloride, europium chloride, boric acid and deionized water.
2. A rare earth modified silicone rubber radiation resistant adhesive as claimed in claim 1, wherein: The de-alcoholized single-component room temperature vulcanized silicone rubber is silicone rubber GD414.
3. A rare earth modified silicone radiation resistant adhesive as claimed in claim 1, wherein: The molar ratio of the gadolinium chloride, samarium chloride, europium chloride and boric acid is 3-4:3-4:2-3:
20.
4. A rare earth modified silicone radiation resistant adhesive as claimed in claim 3, wherein: The molar ratio of the gadolinium chloride, samarium chloride, europium chloride and boric acid is 4:3:3:
20.
5. A rare earth modified silicone radiation resistant adhesive as claimed in claim 1, wherein: The anti-radiation rare earth compound is prepared by mixing mixed rare earth compound, deionized water and complex rare earth coupling agent in a mass ratio of 10:90:0.08, and the mixed rare earth compound is prepared by reacting raw materials including gadolinium chloride, samarium chloride, europium chloride, boric acid and deionized water.
6. A process for the preparation of the rare earth modified silicone rubber radiation resistant adhesive according to any one of claims 1 to 5, characterized in that: The method comprises the following steps: (1) preparing the mixed rare earth compound; (2) mixing the prepared mixed rare earth compound with deionized water, adding the complex rare earth coupling agent OT6080, and then sequentially performing stirring, ultrasonic treatment, suction filtration, hot deionized water washing and drying until a constant weight is obtained to obtain the anti-radiation rare earth compound; (3) mixing the anti-radiation rare earth compound with the de-alcoholized single-component room temperature vulcanized silicone rubber in a nitrogen atmosphere to obtain the rare earth modified silicone rubber anti-radiation adhesive.
7. The production method according to claim 6, characterized by: The step (1) comprises: A. adding a mixed dispersant composed of PEG-20000 and PEG-6000 into deionized water, heating to 94-96 ℃, maintaining and stirring for 10-20 min, and cooling to room temperature; B. adding an aqueous solution of gadolinium chloride, samarium chloride, europium chloride and boric acid into the material obtained in step A, stirring and mixing uniformly until a transparent solution is obtained, and sealing and storing at 38-42 ℃ for 40-50 h; C. adding NaOH solution dropwise into the material obtained in step B, adjusting the pH of the solution to 9-10, stirring uniformly, and sealing and reacting at 4-6 ℃ for 20-30 h; D. performing hydrothermal reaction on the material obtained in step C at 500-800 ℃ for 45-50 h; after the reaction is completed, cooling to room temperature, and then sequentially performing suction filtration and hot water washing to obtain the mixed rare earth compound.
8. The production method according to claim 7, characterized by: The ratio of boric acid to deionized water in the aqueous boric acid solution is 0.2 mol:49.6 g.
9. The production method according to claim 7, wherein: The mixed dispersant is composed of PEG-20000 and PEG-6000 in a mass ratio of 1:0.
24.
10. The production method according to claim 7, wherein: The cooling rate of the cooling to room temperature is 5 ℃ / min.